Prognostic Value of Melanoma Inhibitory Activity Protein in Localized Cutaneous Malignant Melanoma - Angela Sandru; Eugenia Panaitescu; Silviu Voinea; Madalina Bolovan; Adina Stanciu; Sabin Cinca; Alexandru Blidaru (Journal of Skin Cancer)
Background. Cutaneous malignant melanoma (CMM) is a heterogeneous disease, acknowledged for its lack of predictability regarding clinical evolution. In order to appreciate a patient’s individual prognosis, an attempt is made to find new tumor markers that parallel the disease progression. Objective. To identify if melanoma inhibitory activity (MIA) protein could represent a tool for selecting high risk early stages melanoma patients. Method. Between 2008 and 2013, 155 patients with CMM were treated in our clinic. 84 of them were classified into stages I and II, according to TNM 2009. MIA serum concentration was measured in all patients and 50 healthy donors. A cut-off value of 9.4 ng/ml was established using the ROC curve. Results. All patients were followed up by periodic investigations every 6 months. We have noticed that 66% of patients with MIA serum values at diagnosis greater than 9.4 ng/mL have relapsed, while only 5% of patients with MIA serum concentration below the estimated threshold, recurred during the follow-up period (P=0.000). The death risk was 12 times higher in pathological MIA group of patients (P=0.0001). Conclusions. Our data suggest that MIA is an independent prognostic factor for patients with localized CMM.